2008
DOI: 10.1007/s12185-008-0076-5
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of BCL2A1-restricted minor histocompatibility antigens in melanoma cells: application for allogeneic transplantation

Abstract: It has been shown that allogeneic hematopoietic stem cell transplantation (HSCT) can be one of the therapeutic options for patients with metastatic solid tumors, such as renal cancer. However, the development of relatively severe GVHD seems to be necessary to achieve tumor regression in the current setting. Thus, it is crucial to identify minor histocompatibility antigens (mHags) only expressed in tumor cells but not GVHD target organs. In this study, we examined whether three mHags: ACC-1 and ACC-2 encoded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
(35 reference statements)
0
13
0
2
Order By: Relevance
“…Those data also suggested site-specific expression, with higher levels of BCL2A1 found in laryngeal tumours than tumours of the oral cavity, oropharynx or hypopharynx and no correlation with stage or survival (43). BCL2A1 is normally restricted to the haematopoietic compartment, but over-expression has been seen in a number of non-haematological malignancies including bladder cancer, skin cancer and melanomas (44)(45)(46). The over-expression of BCL2A1 in our samples did not seem to be due to inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Those data also suggested site-specific expression, with higher levels of BCL2A1 found in laryngeal tumours than tumours of the oral cavity, oropharynx or hypopharynx and no correlation with stage or survival (43). BCL2A1 is normally restricted to the haematopoietic compartment, but over-expression has been seen in a number of non-haematological malignancies including bladder cancer, skin cancer and melanomas (44)(45)(46). The over-expression of BCL2A1 in our samples did not seem to be due to inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of hematologic malignancies, the therapeutic potential of T cells specific to mHAgs presented predominantly or exclusively on recipient target hematopoietic cells (including leukemia cells) but not on non-target non-hematopoietic cells has been shown via the graft-vs.-leukemia effect following donor lymphocyte infusion against recurring hematological malignancies (2)(3)(4). In addition, some mHAgs such as HA-1 and BCL2A1 have been found expressed in solid tumors, supporting the clinical applicability of immunotherapy in the allo-HSCT setting (5,6). However, it is not always possible to selectively expand mHAg-specific T cells for their use in adoptive immunotherapy, primarily because of the cumbersome and time-consuming in vitro expansion procedure, which sometimes results in T cell exhaustion (7,8).…”
Section: Introductionmentioning
confidence: 90%
“…Several studies show a temporal correlation between clinical response of leukemia and the presence of HA-1 specific T cells in donor blood (detected by MHC/peptide tetramer analysis and other techniques) following allogeneic HCT with or without donor lymphocyte infusion [166168]. There is low-to-absent gene expression of HA-1 in nonhematopoietic cells [169171], HA-1 H -positive non-hematopoietic cells are not recognized by HA-1 H -specific T cells in cellular assays [48], and HA-1 H -specific T cells do not induce tissue damage when cocultured with HA-1 H positive skin in an explant model [172]. It should be noted that hematopoietic cells of recipient origin may remain in the patient’s tissues for 2–3 months after HCT, and one study observed a temporal relationship between the presence of HA-1-specific T cells and acute GVHD [173].…”
Section: Mhc-dependent Tumor-associated Antigensmentioning
confidence: 99%